A Family Financial Planning Strategy - Erligena Br Sebayang; Rindi Andika; Hasrul Azwar Hasibuan (CERED Indonesia Institute, 2022)
The purpose of this study was to determine the understanding of family household management, to determine the application of management to budgeting, to determine the obstacles in the application of family financial management and to see whether there is an influence of internalization on family financial management in the Berastagi area, whose income depends on the production of vegetables, fruits. fruit and tourism. This form of research uses descriptive research with a qualitative approach. The research used descriptive method. The results showed that the family's understanding of family financial planning was still not optimal. The reasons for not making financial planning are 1. uncertain income, still uneven level of education. Lack of interest in making financial planning by doing consistent financial planning for three months.